Requirements for future quantum workforce – a Delphi study - Gerke, Franziska; Müller, Rainer; Bitzenbauer, Philipp; Ubben, Malte; Weber, Kim Alessandro (Journal of Physics: Conference Series, 2022)
With new quantum technologies and new applications comes a new need for specialists, the new quantum workforce. This brings new challenges for education that the typical quantum mechanics courses for physicists do not address. Requirements for the future quantum workforce need to be collected and training programmes created. In between, there should be a European competence framework on which to build the training programmes. One goal of the European Flagship project QTEdu is to develop this framework for second-generation quantum technologies. The Delphi study presented here serves as a basis for this: The aim is to identify knowledge and competences in the field of quantum information technologies, which are partly already needed in industry today, but especially in the future.<br